Influence of Periodontitis in the Development of Nosocomial Pneumonia: A Case Control Study. Issue 5 (1st May 2014) - Gomes‐Filho, Isaac Suzart; Leitão de Oliveira, Thais Feitosa; Seixas da Cruz, Simone; de Santana Passos‐Soares, Johelle; Trindade, Soraya Castro; Oliveira, Michelle Teixeira; Souza‐Machado, Adelmir; Cruz, Álvaro Augusto; Barreto, Maurício Lima; Seymour, Gregory John
Abstract : Background: Although a number of studies on the role of periodontitis in the development of nosocomial pneumonia (NP) have been published, the debate surrounding the existence and nature of this association continues. The present study investigates the influence of periodontitis in NP. Methods: This case‐control study involved 315 individuals: 85 cases (with NP) and 230 controls (without NP), at a general hospital in Feira de Santana, Bahia, Brazil. Sociodemographic characteristics, health conditions, and lifestyle habits were recorded. A full‐mouth periodontal examination was performed and periodontal condition assessed. The diagnosis of NP was made in accordance with established medical criteria, after physical, microbiologic, and/or radiographic examination. Logistic regression was used to calculate the strength of the association between periodontitis and NP. Results: Individuals with periodontitis were three times as likely to present with NP (unadjusted odds ratio [ORunadjusted ] = 3.06, 95% confidence interval [95% CI]: 1.82 to 5.15) as those without periodontal disease. After adjusting for age, time between hospitalization and data collection, last visit to dentist, smoking habit, and present occupation, the association measurement had a slight decrease (ORadjusted = 2.88, 95% CI: 1.59 to 5.19), but the results continued to be statistically significant. Conclusion: These findings suggest that periodontal infection may influence the development of NP, highlighting that periodontitis is a factor positively associated with this respiratory tract infection.